2021
DOI: 10.1002/adbi.202101066
|View full text |Cite
|
Sign up to set email alerts
|

The Knowns and Unknowns about Epididymal Extracellular Vesicles in Different Animal Species

Abstract: Sperm maturation during epididymal transit is a long and complex process. Although the roles of epididymal extracellular vesicles (EVs) on sperm quality have been extensively studied in recent years, there are still a lot of unexplored areas and too few species that are studied. The objective of this review is to focus on the contribution of epididymal EVs through the apocrine secretion of key factors, including proteins and small RNAs. Furthermore, the authors explore the alterations in the content of these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…As we recently reviewed, there are still many unknows regarding epididymal EVs in many different species [ 54 ]. However, the present findings improve our understanding of a key sperm protein carried by EVs that is involved in successful sperm–oocyte interactions and fast completion of the first cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…As we recently reviewed, there are still many unknows regarding epididymal EVs in many different species [ 54 ]. However, the present findings improve our understanding of a key sperm protein carried by EVs that is involved in successful sperm–oocyte interactions and fast completion of the first cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first such recognized interactions involved the transfer of EVs from epididymal cells to spermatozoa undergoing maturation within the epididymis [ 7 ]. Since then, EVs have been analyzed in detail using mass spectrometry and are now known to contain many proteins and diverse species of RNA [ 8 ]. The two EV studies reported in this Special Issue confirmed that EVs function to modulate the physiology of the mammalian female reproductive tract, and besides participating in embryo development and implantation, they can be used to enhance in vitro embryo development and modulate embryo transcription after embryo transfer [ 5 , 6 ].…”
mentioning
confidence: 99%